Prinsip Kekuasaan, Musyawarah, dan Keadilan sebagai Dasar Kenegaraan Perspektif Quraish Shihab dalam Tafsir Al-Misbah - Fanani, Mochammad Rizal; Syahputra, Afrizal El Adzim; Rifa'i, Muhammad Rizal (Study Program of Arabic Language Teaching, 2025)
This study examines the political interpretation in M. Quraish Shihab's Tafsir Al-Misbah, using a library research approach and qualitative content analysis, to explore how the basic principles of state life, such as power, deliberation, and justice, are interpreted from an Islamic perspective. The novelty of this study lies in the effort to contextualize Quraish Shihab's thoughts within the landscape of modern Indonesian statehood and position the interpretation as a source of moderate and inclusive Islamic political values. Beyond analyzing the text, this study also reconstructs the relevance of the interpretation's values to the challenges of democracy, pluralism, and law enforcement in the contemporary era. The findings show that Quraish Shihab offers an Islamic narrative emphasizing the ethics of power, substantive justice, and openness to diversity as basic principles of national life. This study is expected to be an important reference for integrating Islamic values into national political discourse. For further development, a comparative study with other contemporary interpretations or an interdisciplinary approach involving political science and sociology is recommended to expand the usefulness of this research result.